The effects of community-based education programs on empathy, emotional intelligence, and caring behaviors among nursing students: a scoping review - Jing, Ma; Chui, Pinglei; Chong, Mei Chan; Maoting, Tang (Frontiers in Medicine, 2024)
IntroductionCommunity-based learning approaches are gaining recognition in nursing education as a means to address the needs of aging societies by fostering empathy, emotional intelligence, and caring behaviors among nursing students. These attributes are essential for enhancing the quality of care and building strong interpersonal connections with older adults. While community-based education programs offer promising benefits, there is still limited understanding of their impact on nursing students’ empathy, emotional intelligence, and caring behaviors. This scoping review aims to examine how community-based educational interventions can assist nursing students in developing these essential competencies, ultimately contributing to better outcomes in geriatric care.MethodA scoping review was conducted following the framework of Arksey and O’Malley. The following electronic databases were searched: Cumulative Index to Nursing and Allied Health Literature (CINAHL), MEDLINE, Web of Science, Psychology and Behavioral Sciences Collection, PubMed, and Google Scholar. Gray literature was also searched through Google Scholar and ProQuest. Studies included reports on nursing students’ emotional changes due to educational engagements with older adults.ResultsA total of 3,001 abstracts were screened, with 78 full texts reviewed, resulting in 9 studies being included in the analysis. The results demonstrate that interactions with older adults enhance nursing students’ empathy and emotional intelligence while fostering positive changes in their caring behaviors. Participants reported greater sensitivity to the feelings and physical discomforts of older adults, contributing to improved care and stronger relational dynamics.DiscussionCommunity-based education programs involving older adults represent an effective strategy for enhancing nursing students’ empathy, emotional intelligence, and caring behaviors, suggesting valuable implications for nursing education methodologies.